2011
DOI: 10.1111/j.1708-8240.2011.00465.x
|View full text |Cite
|
Sign up to set email alerts
|

Enamel and Dentin Bond Strengths of a New Self-Etch Adhesive System

Abstract: OptiBond XTR, a new two-step self-etch adhesive system, is a promising material for bonding to enamel as well as to dentin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 17 publications
5
35
1
2
Order By: Relevance
“…Two-step self-etch adhesives have been further developed in recent years, and two two-step self-etch adhesives, OptiBond XTR (Kerr, Orange, CA, USA) and Clearfil SE Bond 2 (Kuraray Noritake Dental), have been introduced to the profession with the claim that they exhibit superior bonding performance to the previous generations of two-step self-etch adhesives, including Clearfil SE Bond. In the literature, Walter et al 17) and Meharry et al 18) reported that Optibond XTR showed superior enamel bond strength compared to Clearfil SE Bond. In addition, Sato et al 19) reported that the bond strength after 24 h and long-term (6 month and 1 year) water storage of Clearfil SE Bond 2, which is offered as an improved version of Clearfil SE Bond with a new photo-initiator, was higher than that of Clearfil SE, and that it showed a higher degree of conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Two-step self-etch adhesives have been further developed in recent years, and two two-step self-etch adhesives, OptiBond XTR (Kerr, Orange, CA, USA) and Clearfil SE Bond 2 (Kuraray Noritake Dental), have been introduced to the profession with the claim that they exhibit superior bonding performance to the previous generations of two-step self-etch adhesives, including Clearfil SE Bond. In the literature, Walter et al 17) and Meharry et al 18) reported that Optibond XTR showed superior enamel bond strength compared to Clearfil SE Bond. In addition, Sato et al 19) reported that the bond strength after 24 h and long-term (6 month and 1 year) water storage of Clearfil SE Bond 2, which is offered as an improved version of Clearfil SE Bond with a new photo-initiator, was higher than that of Clearfil SE, and that it showed a higher degree of conversion.…”
Section: Introductionmentioning
confidence: 99%
“…However, with any kind of simplification in clinical application procedure, there arises a concern in loss of bonding 7) . During the last decade, numerous studies were carried out to investigate the efficiency, durability, and robustness of contemporary bonding agents by evaluating their shear bond strength or tensile bond strength 6,[10][11][12][13][14][15] . While most TSERs 11) , TSSEs 11) , and AASs 12) were found to be suitable for orthodontic use, flowable composites failed to provide sufficient bonding strength for bracket attachment 12,16) .…”
Section: Introductionmentioning
confidence: 99%
“…However, clinicians have a tendency to use adhesive systems with simple application procedures. (18) Based on the results of the present study, surface pretreatment with 37% PA accompanied by self-etching adhesive systemsinc reasessh earbond strength in vitro. This method can be further studied in clinical settings.…”
Section: Resultsmentioning
confidence: 99%
“…(17) However, clinicians have a tendency to use adhesive systems with simpler application procedures. (18) Gardner et al compared enamel etch patterns achieved on orthodontic bonding areas treated with PA and nitric acid (NA) using different etch times. The findings suggested that the use of PA provides a better quality etch than NA for all three application times.…”
mentioning
confidence: 99%